A.I. is only Human: Can we keep our flaws out of artificial intelligence and its decision-making? - Chicago Booth Review (Chicago Policy and Markets, 2019)
this journal is a reviews of Artificial intelligence in Economics and Finance.
s
ijb, 13/02/2020
Loan
Keywords: Artificial intelligence; Economics; Finance